2015
DOI: 10.1097/sap.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

How Does Volume of Resection Relate to Symptom Relief for Reduction Mammaplasty Patients?

Abstract: We found that reduction mammaplasty has a positive impact on a range of symptoms, even with lower volume resections and regardless of body surface area-calculated adjustments. This adds further weight to the argument that patients should not be denied access to the surgery based on arbitrary volume restrictions. We advocate freedom for the surgeon to make a decision on potential benefits of surgery based around the needs of each individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
1
27
0
2
Order By: Relevance
“…Our ndings also demonstrated that all patients had a signi cant improvement in pain following surgery and this improvement in pain was unaltered at 6 months post procedure. These ndings of improvement in pain and outcome are consistent with similar studies performed on this subject [16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Our ndings also demonstrated that all patients had a signi cant improvement in pain following surgery and this improvement in pain was unaltered at 6 months post procedure. These ndings of improvement in pain and outcome are consistent with similar studies performed on this subject [16][17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Alternatively, a one-band size increase (e.g. [12][13][14] with no change in cup size is also a 1-point increase in BSS. In a subset of 119 participants, 42 BSSs derived from self-reported bra size data correlated significantly (r = 0.8, p < 0.001) with BSSs derived from investigator measured under and over bust circumferences.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing breast size, noted by women as they get older, may be particularly problematic for women’s health and psychological wellbeing if the burden associated with large breasts that has been suggested in prior work is considered. Increased breast size has previously been related to reduced health and psychological wellbeing in studies of women undergoing reduction mammoplasty surgery where a range of negative physical 1214 and psychological characteristics 1322 have been attributed to having large or excessively large (hypertrophic) breasts. Characteristics that have been most widely examined and which show improvement following reduction mammoplasty include low quality of life, 16,17,19,21,23 body dissatisfaction, 15 low breast satisfaction, 16,19,24 depression, 18,20 upper back pain 14,25 and physical activity limitations.…”
Section: Introductionmentioning
confidence: 99%
“…25 The evidence demonstrates that resection weight does not accurately predict patient-oriented outcomes such as alleviation of pain and related symptoms, and should not be the primary determinant of medical necessity. 2,3,8–10,24,27–31…”
Section: Recommendationsmentioning
confidence: 99%
“…25 The evidence demonstrates that resection weight does not accurately predict patient-oriented outcomes such as alleviation of pain and related symptoms, and should not be the primary determinant of medical necessity. 2,3,[8][9][10]24,[27][28][29][30][31] The Breast Reduction Assessment of Value and Outcomes study proposed a new symptombased definition of medical necessity for reduction mammaplasty. 25 It recommends a simplified instrument, the Physical Symptoms Count, to The presence of two or more of these symptoms, occurring most or all of the time, successfully differentiated a group of reduction mammaplasty patients from a control group containing both nonhypertrophic and hypertrophic subjects: 89.9 percent of operative subjects reported experiencing two or more symptoms all or most of the time, compared with only 2 percent of normal controls.…”
Section: Rationalementioning
confidence: 99%